La maternidad subrogada en el Ecuador y los derechos de los intervinientes. - Leiva Torres, Tatiana Mishell (2023)
The aim of this research is to carry out a legal and doctrinal analysis of surrogate maternity and the right of the intervention in Ecuador, in such a way that it will cover issues related to rental belly, human fertilization and assisted human reproduction, so that the present work will comprise three units for a better understanding, in such a sense that: The first unit will address the concepts, characteristics, procedures and everything related to regulations related to surrogate maternity in the Constitution of the Republic of Ecuador. In the second unit we will analyze surrogate maternity in comparative law taking as a starting point Latin American countries as of Europe, information that will serve us to know the legal reality that each country manages regarding this topic. Unit three will determine the relevance of the implementation of legal reforms in Ecuadorian legislation due to the great delay that exists in the country compared to the new techniques of assisted reproduction that are developed. The results obtained will show the urgency of legislating this problem, since it is currently a practice that is being carried out in our country in a clandestine way due to the lack of regulations that exist, in which they establish the limits that must be carried out.